The Androgen Receptor Bridges Stem Cell-Associated Signaling Nodes in Prostate Stem Cells - Alastair H. Davies; Amina Zoubeidi (Stem Cells International)
The therapeutic potential of stem cells relies on dissecting the complex signaling networks that are thought to regulate their pluripotency and self-renewal. Until recently, attention has focused almost exclusively on a small set of “core” transcription factors for maintaining the stem cell state. It is now clear that stem cell regulatory networks are far more complex. In this review, we examine the role of the androgen receptor (AR) in coordinating interactions between signaling nodes that govern the balance of cell fate decisions in prostate stem cells.